2021
DOI: 10.1088/1742-6596/1882/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Termiticidal and Nematicidal activities of five extracts from Garlic (Allium sativum)

Abstract: Garlic (Allium sativum Linn) has been known and used as therapeutic agents to prevent several pathologies diseases. The aim of this study is to evaluate the effects of five garlic extracts, namely, aqueous garlic extract (AGE), methanol garlic extract (MGE), ethyl acetate garlic extract, EAGE), and n-hexane garlic extract (HGE) against root-knot nematode, Meloidogyne sp. and termite, Nasutitermes sp. The nematicidal and termiticidal activities of five garlic extracts were performed at concentration of 10; 25; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Researchers have long studied plant extracts for their broad spectrum of medicinal properties such as anti-inflammatory [1], antibacterial [2,3], antifertility [4], termiticide, and nematicide activities [5]. Studies on plant extracts have recently gained more interest during the COVID-19 pandemic in the effort to find efficacious antiviral agents [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have long studied plant extracts for their broad spectrum of medicinal properties such as anti-inflammatory [1], antibacterial [2,3], antifertility [4], termiticide, and nematicide activities [5]. Studies on plant extracts have recently gained more interest during the COVID-19 pandemic in the effort to find efficacious antiviral agents [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Diallyl disulfide iswhich are the primary sulfur compounds, can effectively control the occurrence of bean root rot, tomato root-knot nematode, and pepper blight (Avato et al 2000, Ma et al 2009). Khairan et al (2021) found that all garlic extracts in their study contained flavonoids, alkaloids and saponin secondary metabolites and showed that ethyl acetate garlic extracts had the highest nematicidal activity against root-knot nematodes. Galisteo et al (2022) identified the nematicidal components of garlic oil as diallyl disulfide and diallyl trisulfidine and cited it as an important resource for the development of new nematode control products.…”
Section: Resultsmentioning
confidence: 98%
“…It is possible to note that EOs derived from A. sativum and T. vulgaris can be marked as the most used oils against different PPNs. Several studies have shown that garlic extracts are known to have antibacterial [ 83 ], antifungal [ 84 ], and nematicidal activities [ 85 ]. The abundance of organosulfur compounds such as alliin, allicin (S-allylcysteine sulfoxide) and some polysulfanes (diallysulfide, diallyldisulfide, diallyltrisulfide, diallyltetrasulfide) give garlic EO robust activity against multiple problems and they have been reported as green pesticides [ 86 ].…”
Section: Resultsmentioning
confidence: 99%